2022
DOI: 10.1080/10717544.2022.2044938
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of curcumin analog nano-bilosomes using 21.31full factorial design for anti-tumor profiles improvement in human hepatocellular carcinoma:in-vitroevaluation,in-vivosafety assay

Abstract: Curcumin (CU) is a natural polyphenolic phytoingredient. CU has anti-inflammatory, anti-oxidant, and anticancer activities. The poor solubility, bioavailability, and stability of CU diminish its clinical application. Hence, structural modification of CU is highly recommended. The CU analog; 3,5-bis(4-bromobenzylidene)-1-propanoylpiperidin-4-one (PIP) exhibited high stability, safety, and more potent antiproliferative activity against hepatocellular carcinoma. In the present study, nano-bilosomes (BLs) were for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…It is worth noting that, although a negatively charged surface might slightly affect the cellular internalization, the stability of nano-systems against aggregation is crucial for benefiting from the nano-size. In addition, many studies have reported enhanced anticancer activity for negatively charged nanoformulation [ 44 , 45 , 46 , 47 ]. Accordingly, the study aimed at maximizing the absolute ZP value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that, although a negatively charged surface might slightly affect the cellular internalization, the stability of nano-systems against aggregation is crucial for benefiting from the nano-size. In addition, many studies have reported enhanced anticancer activity for negatively charged nanoformulation [ 44 , 45 , 46 , 47 ]. Accordingly, the study aimed at maximizing the absolute ZP value.…”
Section: Resultsmentioning
confidence: 99%
“…The reported size was sufficient for tumor-specific accumulation. Abbas et al reported an enhanced cytotoxic effect for optimized curcumin bilosomes with maximized negative absolute zeta potential of −27.05 mV [ 46 ]. On the other hand, previous studies that involve vesicles with higher size in the micro range exhibited low cytotoxicity profiles on different cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Natural plant drugs are used for anti-HCC treatment because of their low toxicity, but most of them have poor water solubility that limits their wide application. 185 Curcumin (CU) is an anti-inflammatory and anti-cancer natural polyphenolic plant component with enhanced solubility and anti-cancer effects, which was modified into nano vesicles by Abbas et al 186 Similarly, CU mitochondrial delivery system based on polyamide dendrimer molecules increase mitochondrial ROS levels and induce apoptosis at lower doses. 187 GA LPs interfere with various signaling proteins involved in HCC pathogenesis, altering.…”
Section: Treatmentmentioning
confidence: 99%
“…Curcumin (Cur) is a polyphenol that can be isolated from samples of turmeric root [ 1 ]. Prior research has demonstrated that Cur possesses a range of anti-tumor [ 2 , 3 ], anti-cancer [ 4 , 5 ], anti-inflammatory [ 6 ], antioxidant [ 7 ], and anti-ischemic [ 8 ] pharmacological properties. In the context of tumor treatment, Cur has been shown to be capable of inducing apoptotic tumor cell death inhibiting the proliferative and invasive activity of these cells [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%